MODIFICATION OF AMINO ACIDS AT SHOCK PRESSURES OF 3.5 TO 32 GPA - Peterson E.; Horz F.; Chang S. (My University, 1997)
Amino acids were subjected to shock impact over a pressure range of 3.5 to 32 GPa both within and without meteoritic mineral matrices. The extent of amino acid destruction, racemization, and conversion to secondary amino acids was examined. Abundances of parent compounds decreased by a factor of 103 over this pressure range. Racemization also occurred, but some residual optical activity remained in the amino acids surviving shocks up to 32 GPa. Secondary amino acids formed in the high peak pressure range; those identified were β-alanine, glycine, alanine, γ-aminobutyric acid, and β-aminoisobutyric acid. At 30 GPa, the abundances of these daughter compounds exceeded those of the remaining initial amino acids. As the concomitant effects of high mechanical stress and temperature accompanying shocks cannot be separated in this work, their relative contribution to the observed transformations cannot be estimated. The survival of amino acids in shock experiments suggests that, after formation or emplacement of amino acids in carbonaceous chondrite parent bodies, these objects never experienced impact velocities greater than 5 km/s, which suffices to generate 30 GPa for typical silicate/silicate impacts. These results also provide guidelines for choosing appropriate capture media for interplanetary dust particles on Earth-orbiting platforms.